AN INTRODUCTORY APPROACH TO THE TEACHING OF THE CULTURAL ASPECTS OF ENGLISH - María D. Milla Lara (European Scientific Journal, ESJ, 2014)
Over the last decades, new approaches to language teaching are aiming for a more participative and interactive language experience. Moreover, an increasingly globalised world fosters interaction between different cultures. Bearing these facts in mind, this paper firstly examines the generally poor level of intercultural awareness that there exists amongst secondary school students. Secondly, it focuses on the potential positive effects that an approach to cultural elements in the FL class would perform on our students and on our society. Thirdly, it suggests some ideas to implement culture teaching in the classroom. In fast-changing societies such as ours, we need highly culturally competent individuals to face the challenges to come, and an appropriate way to do this is through language education.